Urban dynamicsinmoderndimension (Journal of Philosophy, Culture and Political Science, 2016)
This article discusses the nature and appearance of cities, manifestations of the phenomenon of urban culture. First, it analyses the features of cities in the various stages of the development of society. Second, it assesses the changing role of the modern city. Third, urban development and the changing role of capital in modern Kazakhstan. The authors examines the city as part of a variety of socio-economic systems. Formulated theoretical and methodological approaches used to study the major trends and issues of socio-economic dynamics of cultural cities. The authors analyzes the current state of urban culture and cultural values of cities in the world development. In conclusion, the authorsdevelop their ownunderstanding of the roleof Astana in thecultural and civilizationaldevelopment of Kazakhstan.